Authentic-Inquiry-Project about Nyale on Science Teachers Critical and Creative Thinking Skills - Kerans, Geterudis; Sanjaya, Yayan; Liliasari, Liliasari; Ghanggo Ate, Yustinus (Universitas Negeri Semarang, 2024)
The aim of this study was to determine the effect of authentic inquiry project practicum on Nyale in improving critical and creative thinking skills of prospective science teacher students. The method used was experimental research method with one group pretest postest. The research subjects involved science education students of one of the universities in Sumba in the 2023/2024 academic year who contracted animal anatomy and physiology courses. The instrument used in this research was a critical and creative thinking skills test. The results of the Wilcoxon test showed that in experimental classes 1 and 2 there was an effect of practicum on the critical and creative thinking skills of prospective science teacher students as evidenced by the Asymp. Sig. (2-tailed) 0.000 < than 0.05. In addition, the N-gain test results showed an increase in critical thinking skills before and after practicum in experimental classes 1 and 2 with moderate categories. While the N-gain test of creative thinking skills showed an increase in the creative thinking skills of prospective science teachers in the moderate category for experimental class 1 and in the low category for experimental class 2. From the results obtained, it can be concluded that the authentic inquiry project practicum on Nyale is effective in improving the critical and creative thinking skills of prospective science teachers.